TECHNICAL GUIDANCE FOR INCREASING BUSINESS PRODUCTIVITY AND INCOME OF COASTAL COMMUNITIES THROUGH THE IMPLEMENTATION OF AGRIBUSINESS MANAGEMENT - Dr. Jopinus Saragih; Nurmala; Yunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Communities in coastal and marine areas generally depend on fishing, especially capture fisheries (fishermen). The potential for fishery resources in coastal areas is quite large, but some people in these areas are still below the poverty line.With the difficulty in getting capital from the cooperative, SME entrepreneurs are looking for other alternatives by borrowing money from relatives and or middlemen. However, middlemen in most cases actually ensnare SME entrepreneurs, namely in the form of providing loans at high interest rates (18 – 30% per year). Thus, the objective of developing capital associated with business development cannot be achieved. Achievement of the target of mastering the material, all participants can follow the entire training process from start to finish, and the activities designed are 100% implemented. The target for delivering training material was also achieved because the material could be delivered as a whole. Thus, the objectives of technical guidance activities can be fulfilled.